2017
DOI: 10.1021/acs.energyfuels.6b03143
|View full text |Cite
|
Sign up to set email alerts
|

Key Findings of the World’s First Offshore Methane Hydrate Production Test off the Coast of Japan: Toward Future Commercial Production

Abstract: Marine methane hydrate in sands has huge potential as an unconventional gas resource; however, no field test of their production potential had been conducted. Here, we report the world's first offshore methane hydrate production test conducted at the eastern Nankai Trough and show key findings toward future commercial production. Geological analysis indicates that hydrate saturation reaches 80% and permeability in the presence of hydrate ranges from 0.01 to 10 mdarcies. Permeable (1−10 mdarcies) highly hydrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
260
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 544 publications
(262 citation statements)
references
References 38 publications
1
260
0
1
Order By: Relevance
“…In nature, the dominant gas in NGH is methane, which forms at low temperature and high pressure with extensive distribution in the permafrost and in deep marine sediments [1,3,4]. The evaluation results show that the global quantity of hydrocarbon gas hydrates varies widely between 10 15 and 10 18 ST m 3 (ST represents the standard conditions) [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In nature, the dominant gas in NGH is methane, which forms at low temperature and high pressure with extensive distribution in the permafrost and in deep marine sediments [1,3,4]. The evaluation results show that the global quantity of hydrocarbon gas hydrates varies widely between 10 15 and 10 18 ST m 3 (ST represents the standard conditions) [2,5].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple methods have been proposed and employed to decompose hydrate for gas recovery from the HBS, such as depressurization, thermal stimulation, gas exchange, and the use of hydration inhibitors (such as salts and alcohols) [2,[5][6][7][8]. The above methods have been compared in terms of energy efficiency, economic and technological feasibility, and environmental performance [1,4,9,10]. Past laboratory and field tests and numerical studies showed that depressurization is the most potential method for gas recovery from HBS, while the other methods may be suitable for enhancing recovery or reservoir stimulation [4,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations